THU0329 Autoantibodies to GABAB Receptors Detected in Patients with Systemic Lupus Erythematosus. (23rd January 2014) - Tsuchiya, H.; Haga, S.; Takahashi, Y.; Ishizaka, Y.; Mimori, A.
Abstract : Background: The gamma-aminobutyric acid receptor type B (GABARB ) is a G-protein-coupled receptor involved in signal transduction by GABA, an inhibitory neurotransmitter. GABARB comprises two subunits: GABARB1 and GABARB2 . Interestingly, these subunits were identified as target antigens in stiff person syndrome and limbic encephalitis 1 -3 ) . To identify novel candidate antigens in patients with systemic lupus erythematosus (SLE), we explored a random peptide display library using serum samples of these patients and identified GABARB subunits as candidate novel autoantigens in SLE. Objectives: To prove the clinical significance of autoantibodies to GABARB subunits (α-GABARBs ), we first examined the frequency of α-GABARBs in patients with connective tissue diseases. In addition, we focused on the presence of α-GABARBs in patients with SLE and investigated the possible link of α-GABARBs with disease activity and neuropsychiatric symptoms. Methods: An enzyme-linked immunosorbent assay (ELISA) was performed with recombinant Flag-tagged proteins of GABARB1 (1–475 amino acids (aa)) and GABARB2 (1–480 aa), corresponding to ectodomains of GABARB1b and GABARB2, respectively. Titers of α-GABARBs were obtained by determining the absorbance (Ab) at OD450, which was obtained after reacting with a horseradish peroxidase conjugated second antibody to human IgG. ELISA was first performed on sera from healthy subjects (n = 15) and patients with SLE (n = 88), scleroderma (n = 20), myositis (n = 20), and vasculitis (n = 20). Next, 23 cerebrospinal fluid (CSF) samples from patients with SLE were analyzed in the same manner. The clinical significance of the obtained results was then evaluated on the basis of clinical data of the enrolled patients. Results: The titers of α-GABARB1 and α-GABARB2 in patients with acute-phase SLE were significantly high compared with those in healthy subjects ( P < 0.001, Ab-OD450 = 0.51 vs. 0.09 for α-GABARB1 and 0.48 vs. 0.06 for α-GABARB2, respectively). Notably, more than 80% patients with acute-phase SLE demonstrated higher titers than the maximum value detected in healthy subjects. Moreover, the titers of α-GABARBs in patients with acute-phase SLE (n = 50) were significantly higher than those in patients with chronic-phase SLE (n = 38) ( P < 0.001), which significantly decreased after treatment (n = 8). Strong correlations were observed between titers of α-GABARB1 and α-GABARB2 (rs = 0.87, P < 0.0001), both of which correlated with the titer of α-dsDNA ( P < 0.0001, rs = 0.47 for α-GABARB1 and rs = 0.59 for α-GABARB2 ). Although we did not observe a positive correlation of serum α-GABARBs with neuropsychiatric symptoms, we found that α-GABARB1 and α-GABARB2 were detected in seven of the 16 CSF samples obtained from patients with neuropsychiatric SLE (43.8%). In contrast, no significant high titers of α-GABARBs were detected in serum samples of patients with scleroderma, myositis, and vasculitis. Conclusions: Serum α-GABARBs could be novel markers for patients with active-phase SLE. To correlate α-GABARBs with neuropsychiatric SLE, further investigation would be required to confirm the presence of α-GABARBs in CSF of these patients. References: Curr Opin Neurol. 2012 Dec;25(6):795-801. Lancet Neurol. 2011 Aug;10(8):759-72. Neurology. 2011 Mar 1;76(9):795-800. Disclosure of Interest: None Declared